2012
DOI: 10.1155/2012/294528
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study with regard to the Wound Healing Activity of Protein fromCalotropis procera(Ait.) R. Br.

Abstract: We provide the scientific basis for the use of Calotropis procera for treating skin and wound infections in traditional medicine. The aqueous extract of stem-bark of C. procera exhibited more pronounced potent antimicrobial activity. Calo-protein was purified and identified from the most-active aqueous extracts of C. procera and showed broad-spectrum activity. Calo-protein inhibited the growth of S. aureus and E. aerogenes effectively at 25 μg/ml concentration. Mice topically treated with Calo-protein revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Aiton (Asclepiadoideae), with multifarious medicinal and biological properties (Yesmin et al, 2008), has traditionally been used for the treatment of leprosy, wound infections, tumors, inflammation, fever, and diseases of the spleen and abdomen ( Perumal & Chow, 2012). The findings of the Amin et al (2013) revealed that methanol and acetone extracts of C. procera showed stronger anti-H. pylori activity than metronidazole, almost comparable activity with tetracycline, but were found to be less potent than amoxicillin and clarithromycin.…”
Section: Calotropis Proceramentioning
confidence: 99%
“…Aiton (Asclepiadoideae), with multifarious medicinal and biological properties (Yesmin et al, 2008), has traditionally been used for the treatment of leprosy, wound infections, tumors, inflammation, fever, and diseases of the spleen and abdomen ( Perumal & Chow, 2012). The findings of the Amin et al (2013) revealed that methanol and acetone extracts of C. procera showed stronger anti-H. pylori activity than metronidazole, almost comparable activity with tetracycline, but were found to be less potent than amoxicillin and clarithromycin.…”
Section: Calotropis Proceramentioning
confidence: 99%
“…In previous studies, different extracts were analyzed against these microbes and latex were found effective. A study was performed on the protein separated from stem bark named Cal-Protein and tested against various Gram negative and Gram positive bacteria and it was found effective comparable to chloramphenicol ( Perumal Samy and Chow 2012 ). Similarly, another study was designed in which bioactive proteins were isolated and characterized from fruits of B. pinguin and further this protein was fractionated by gel filtration chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…However, these AMPs act as host defense system and are active against different types of microorganisms either by direct antimicrobial action or by immunomodulatory effects ( Manoury et al, 2011 ). AMPs have been studied against various Gram-positive and Gram-negative bacteria in which these proteins were separated from C. procera bark ( Perumal Samy and Chow 2012 ). In present study, we isolated the pharmacologically active SLPs from latex of this plant, these SLPs are not yet evaluated for antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Topical application of 20 μl of 1.0% sterile solution of the latex of Calotropis procera twice daily was followed for 7 days. The latex significantly augmented the healing process by markedly increasing collagen, DNA and protein synthesis and epithelisation leading to reduction in wound area thus the study provided a scientific rational for the traditional use of this plant in the management of wound healing (Samy and Chow, 2012).…”
Section: Wound Healing Activitymentioning
confidence: 99%